2018
DOI: 10.1101/402065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Description of novel marine bioflocculant-producing bacteria isolated from biofloc of Pacific whiteleg shrimp,Litopenaeus vannameiculture ponds

Abstract: 19Description of marine bioflocculant-producing bacteria isolated from biofloc of 20 Pacific whiteleg shrimp, Litopenaeus vannamei culture ponds was prompted to 21 explore the bacteria that enhanced bioflocculation process in aquaculture wastewater 22 treatment. Certain marine bacteria were potentially secreted extracellular polymeric 23 substances (EPS) which response to the physiological stress encountered in the natural 24 environment that can act as bioflocculants. This study aimed to identify marine 25 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…The identified isolates were dominantly Bacillus sp. which agrees with the findings of Hashim et al (2018). Previous studies have also reported on the presence of bioflocculating bacteria in biofloc culture ponds of P. vannamei (Kasan et al 2016).…”
Section: Resultssupporting
confidence: 91%
“…The identified isolates were dominantly Bacillus sp. which agrees with the findings of Hashim et al (2018). Previous studies have also reported on the presence of bioflocculating bacteria in biofloc culture ponds of P. vannamei (Kasan et al 2016).…”
Section: Resultssupporting
confidence: 91%